ZnuD, a Potential Candidate for a Simple and Universal Neisseria meningitidis Vaccine - Hubert, Kerstin (American Society for Microbiology, 2013)
Neisseria meningitidis serogroup B (MenB) is a major cause of bacterial sepsis and meningitis, with the highest disease burden in young children. Available vaccines are based on outer membrane vesicles (OMVs) obtained from wild-type strains. However, particularly in toddlers and infants, they confer protection mostly against strains expressing the homologous protein PorA, a major and variable outer membrane protein. In the quest for alternative vaccine antigens able to provide broad MenB strain coverage in younger populations, but potentially also across all age groups, ZnuD, a protein expressed under zinc-limiting conditions, may be considered a promising candidate. Here, we have investigated the potential value of ZnuD and show that it is a conserved antigen expressed by all MenB strains tested except for some strains of clonal complex ST-8. In mice and guinea pigs immunized with ZnuD-expressing OMVs, antibodies were elicited that were able to trigger complement-mediated killing of all the MenB strains and serogroup A, C, and Y strains tested when grown under conditions of zinc limitation. ZnuD is also expressed during infection, since anti-ZnuD antibodies were detected in sera from patients. In conclusion, we confirm the potential of ZnuD-bearing OMVs as a component of an effective MenB vaccine.